Microlaparoscopy in Sex Reassignment Surgery. (2004) - De Stefani, S.; Trombetta, C.; Raber, M.; Savaco, G.; Moro, U.; Belgrano, E.
Abstract : Sex reassignment (male to female surgery) is a standard operation which is aimed at constructing female genitalia and obtaining a cosmetic and functional result that is similar to that of a normal female subject. The ideal surgical procedure has not yet been described, but the various techniques which have been proposed in the literature are similar. The most cumbersome maneuver of the procedure is that of creating a neovaginal cavity inside the perineum. This step is generally carried out by means of blunt dissection between the rectal wall and the prostate, but most of the surgery is blindly performed without visual control. In these conditions, the risk of rectal injury is high, and may lead to severe intraoperative complications. Microlaparoscopy allows for a direct observation of the perineal dissection from inside the peritoneal cavity, thus avoiding risk of rectal injury. The technique is simple to perform, is non-invasive, and only 15 minutes are added to the operation.